Menimbang Etika Kecerdasan Buatan: Sebuah Telaah Filosofis tentang Implementasi AI dalam Manajemen Sekolah - Catur Prida Retnivia; Krista Alisa Meyliani; Pratisa Martha Sari; Warman; Muhammad Amir Masruhim; Dwi Nugroho Hidayanto (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
The rapid development of artificial intelligence (AI) presents significant opportunities for improving school management, yet simultaneously raises ethical concerns related to privacy, digital equity, and accountability. This study aims to analyze the readiness for AI implementation in school management across East Kalimantan using a mixed-methods approach that combines empirical dataset analysis with a philosophical review grounded in deontology, utilitarianism, and virtue ethics. The dataset consists of 30 schools and includes variables related to infrastructure readiness, such as the number of computers, internet availability, and AI usage levels (None–High). The findings indicate that 66.67% of schools have internet access; however, AI adoption remains relatively low, with most schools categorized as Low or Medium. These results highlight that infrastructure inequality can create digital injustice in AI deployment. The philosophical analysis emphasizes the need for comprehensive ethical policies, including data protection, algorithmic auditing, and human oversight, to ensure that AI implementation is fair and responsible. The study recommends a phased approach to AI adoption, enhanced technological literacy among educators, and strengthened data governance to ensure AI supports humanistic values and educational equity.